Optimal Scheduling of Refined Products Pipelines with Multiple Sources - Cafaro, Diego Carlos (2009)
Most contributions on short-term planning of multiproduct pipeline operations deal with pipelines featuring a single input terminal. In common-carrier pipelines, however, several refineries located at different sites use the same trunk line for shipping refined petroleum products to downstream output terminals. They can be regarded as multiple-source pipelines with input facilities at non-origin points. The operation of intermediate sources raises some new difficult issues. Pumping runs taking place at intermediate locations can either insert a new lot or increase the size of a batch in transit. Batches are no longer arranged in the line in the same order that they are injected, and tracking the batch sequence becomes a more complex task. This paper introduces a novel continuous formulation for the scheduling of multiple-source pipelines operating on fungible or segregated mode. A case study involving a pipeline with two input and three output terminals, transporting three distillates was successfully solved over a 10-day time horizon.